Development of efficient, reproducible and stable Agrobacterium-mediated genetic transformation of five potato cultivars - Bakhsh, Allah (Array, 2020)
The developments in transformation technology have enabled the scientists to incorporate, mutate or substitute gene(s) leading to a particular trait; advancing it to a point where only few technical limitations remain. Genotype dependency and explant types are important factors affecting transformation efficiency in potato. In the present study, a rapid, reproducible and stable Agrobacterium-mediated transformation procedure in potato was developed by a combination of different plant growth regulators. Leaf discs and internodal explants of five cultivars of potato, i.e. Lady Olympia, Granola, Agria, Désirée and Innovator were infected with Agrobacterium tumefaciens strain LBA4404 containing pBIN19 expression vector with β-glucuronidase gusA gene under the control of 35S CaMV promoter. Kanamycin was used as plant selectable marker for screening of primary transformants at concentration of 100 mg/L. Both explants responded positively; internode being more suitable explant for better transformation efficiency. Based on GUS histochemical assay, the transformation efficiency was 22, 20, 18.6, 15 and 10 % using the internodal explant, and 15, 12, 17, 8 and 6 % using leaf discs as explant in Lady Olympia, Granola, Agria, Désirée and Innovator respectively. Furthermore, PCR assays confirmed the presence of gusA and nptII genes in regenerated plants. The molecular analysis in succeeding progeny showed proper integration and expression of both genes. The results suggest Lady Olympia as the best cultivar for future transformation procedures. Overall, the short duration, rapidity and reproducibility make this protocol suitable for wider application of transgenic potato plants.